A pairwise chemical genetic screen identifies new inhibitors of glucose transport - Ulanovskaya, Olesya A. (2011)
Oxidative phosphorylation (OXPHOS) and glycolysis are the two main pathways that control energy metabolism of a cell. The Warburg effect, in which glycolysis remains active even under aerobic conditions, is considered a key driver for cancer cell proliferation, malignancy, metastasis and therapeutic resistance. To target aerobic glycolysis, we exploited the complementary roles of OXPHOS and glycolysis in ATP synthesis as the basis for a chemical genetic screen, enabling rapid identification of novel small-molecule inhibitors of facilitative glucose transport. Blocking mitochondrial electron transport with antimycin A or leucascandrolide A had little effect on highly glycolytic A549 lung carcinoma cells, but adding known glycolytic inhibitors 2-deoxy-D-glucose, iodoacetate or cytochalasin B, rapidly depleted intracellular ATP, displaying chemical synthetic lethality. Based on this principle, we exposed antimycin A-treated A549 cells to a newly synthesized 955-member diverse scaffold small-molecule library, screening for compounds that rapidly depleted ATP levels. Two compounds potently suppressed ATP synthesis, induced G1 cell-cycle arrest and inhibited lactate production. Pathway analysis revealed that these novel probes inhibited GLUT family of facilitative transmembrane transporters but, unlike cytochalasin B, had no effect on the actin cytoskeleton. Our work illustrated the utility of a pairwise chemical genetic screen for discovery of novel chemical probes, which would be useful not only to study the system-level organization of energy metabolism but could also facilitate development of drugs targeting upregulation of aerobic glycolysis in cancer.